Masa Kemunduran Pendidikan Islam : Analisis Dampak Runtuhnya Baghdad pada Tahun 1258 M - A. Riswan Pratama; Eka Wahyuni; Fatimah Az Zahra; Mahfud Ifendi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education reached its peak during the Abbasid Dynasty, precisely from the eighth to the thirteenth centuries AD. This period is often referred to as the